AMi: a GUI‐based, open‐source system for imaging samples in multi‐well plates. Issue 8 (9th August 2019) - Bohm, Andrew
Abstract : Described here are instructions for building and using an inexpensive automated microscope that is driven by a dedicated graphical user interface. The system facilitates the automated imaging and manual inspection of multi‐well plates. Abstract : Described here are instructions for building and using an inexpensive automated microscope (AMi) that has been specifically designed for viewing and imaging the contents of multi‐well plates. The X, Y, Z translation stage is controlled through dedicated software ( AMiGUI ) that is being made freely available. Movements are controlled by an Arduino‐based board running grbl, and the graphical user interface and image acquisition are controlled via a Raspberry Pi microcomputer running Python. Images can be written to the Raspberry Pi or to a remote disk. Plates with multiple sample wells at each row/column position are supported, and a script file for automated z ‐stack depth‐of‐field enhancement is written along with the images. The graphical user interface and real‐time imaging also make it easy to manually inspect and capture images of individual samples.